2016
DOI: 10.1016/j.kint.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Only minor differences in renal osteodystrophy features between wild-type and sclerostin knockout mice with chronic kidney disease

Abstract: Renal osteodystrophy affects the majority of patients with advanced chronic kidney disease (CKD) and is characterized by progressive bone loss. This study evaluated the effects of sclerostin knockout on bone in a murine model of severe, surgically induced CKD in both sclerostin knockout and wild-type mice. Mice of both genotypes with normal kidney function served as controls. Tibiae were analyzed using micro-computed tomography, and lumbar vertebrae were analyzed by histomorphometry. Results were tested for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…Uremic mice in the current study, as well as in previous studies (50)(51)(52)(53), showed elevated rather than diminished serum 1,25(OH) 2 D 3 levels that are commonly observed in patients with CKD. While increased FGF23 leads to decreased 1,25(OH) 2 D 3 production and secondary hyperparathyroidism in early to moderate CKD (23,54), it fails to exert its physiologic effects in end-stage renal disease.…”
Section: Discussionsupporting
confidence: 78%
“…Uremic mice in the current study, as well as in previous studies (50)(51)(52)(53), showed elevated rather than diminished serum 1,25(OH) 2 D 3 levels that are commonly observed in patients with CKD. While increased FGF23 leads to decreased 1,25(OH) 2 D 3 production and secondary hyperparathyroidism in early to moderate CKD (23,54), it fails to exert its physiologic effects in end-stage renal disease.…”
Section: Discussionsupporting
confidence: 78%
“…A common experimental model for renal failure is 5/6 nephrectomy, and high-phosphate feeding is frequently used to promote secondary hyperparathyroidism and high-turnover renal osteodystrophy. 24,[40][41][42][43] As expected, nephrectomized mice exhibited elevated PTH levels, which were accompanied by increased bone formation and bone resorption parameters. Despite the induction of high-turnover renal osteodystrophy, bone volume paradoxically increased.…”
Section: Discussionsupporting
confidence: 65%
“…The increases in bone volume and serum calcium and 1,25(OH) 2 levels in nephrectomized mice were unexpected but have been observed by other investigators. 24,[40][41][42] One possible reason for the varying metabolic changes observed in nephrectomized mice may be the preserved sensitivity of the remnant kidney to elevated PTH, which could lead to increased 1,25(OH) 2 production and consequent increased bone mass. Our findings, together with previous reports, confirm the difference in mineral and bone metabolism between the nephrectomized mouse model and human CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of the SOST gene or treatment with a sclerostin antibody in mice has rendered conflicting results concerning the association of serum sclerostin with bone turnover [34][35][36]. Possible explanations are differences in experimental methods, sclerostin assays, type of bone, and species specific differences in regulation of bone turnover.…”
Section: Discussionmentioning
confidence: 99%